Kafka - Mairowitz, David Zane. 1943-; Crumb, Robert . 1943-; Appignanesi, Richard (Seattle, Wash. : Fantagraphics, 2007)
Mairowitz's text and Crumb's graphic novel-style illustration help the reader understand Kafka's life and thinking and the phrase "Kafkaesque."
Includes index.
Keywords: Kafka, Franz, -- 1883-1924 -- Biography -- Fiction; Kafka, Franz, -- 1883-1924 -- Comic books, strips, etc; Authors, Austrian -- 20th century -- Biography